Photopolymerized micelles of diacetylene amphiphile: physical characterization and cell delivery properties1. Issue 58 (25th July 2015) - Neuberg, Patrick; Perino, Aurélia; Morin-Picardat, Emmanuelle; Anton, Nicolas; Darwich, Zeinab; Weltin, Denis; Mely, Yves; Klymchenko, Andrey S.; Remy, Jean-Serge; Wagner, Alain
<x xml:space="preserve">Abstract</x> Photopolymerized micelles of diacetylenic amphiphiles bearing polyethylene glycol headgroups allow for enhanced intracellular delivery of hydrophobic dye molecules.